2016
DOI: 10.1073/pnas.1600483113
|View full text |Cite
|
Sign up to set email alerts
|

Budgerigars and zebra finches differ in how they generalize in an artificial grammar learning experiment

Abstract: The ability to abstract a regularity that underlies strings of sounds is a core mechanism of the language faculty but might not be specific to language learning or even to humans. It is unclear whether and to what extent nonhuman animals possess the ability to abstract regularities defining the relation among arbitrary auditory items in a string and to generalize this abstraction to strings of acoustically novel items. In this study we tested these abilities in a songbird (zebra finch) and a parrot species (bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 54 publications
4
60
0
Order By: Relevance
“…The fact that our pigeons' performance was indistinguishable from that of the baboons across four markers of orthographic processing strongly suggests that the ability to process orthographic information is not limited to the primate brain. Our findings add to a growing body of work demonstrating that birds are ideal models with which to investigate the origins of language (38)(39)(40). At the level of the neuronal recycling hypothesis, our findings may represent the most powerful evidence of Dehaene's (1) thesis: that neurons in a visual system neither genetically nor organizationally similar to humans can not only code words but also the statistical properties that define them.…”
Section: Discussionsupporting
confidence: 53%
“…The fact that our pigeons' performance was indistinguishable from that of the baboons across four markers of orthographic processing strongly suggests that the ability to process orthographic information is not limited to the primate brain. Our findings add to a growing body of work demonstrating that birds are ideal models with which to investigate the origins of language (38)(39)(40). At the level of the neuronal recycling hypothesis, our findings may represent the most powerful evidence of Dehaene's (1) thesis: that neurons in a visual system neither genetically nor organizationally similar to humans can not only code words but also the statistical properties that define them.…”
Section: Discussionsupporting
confidence: 53%
“…However, these results do suggest an interesting avenue for further comparative investigation on the neural basis of fine structure and envelope processing in birds. Another recent perceptual study of these zebra finches and budgerigars also showed a difference in both capability and strategy in the processing of sequences of song elements (Spierings and ten Cate 2016). …”
Section: Discussionmentioning
confidence: 95%
“…However, there are differences between species in terms of generalization abilities and preferred learning strategies. For instance, in an artificial grammar learning task, zebra finches (whose songs are highly stereotyped) were found to generalize based on positional relationships, while budgerigars (a parrot species that produces long and variable songs) were able to extract the underlying abstract rules between items [12]. One of the central questions in statistical learning research is how species- or domain-general the underlying learning mechanisms are [18], so it is of particular interest to study statistical learning mechanisms that support a more general ability to vocally learn in order to gain a deeper understanding about the specializations that led to the emergence of human language.…”
Section: Introductionmentioning
confidence: 99%